Conceptualizing bi- and multilingual disciplinary literacies in CLIL: insights from a European research network - Hüttner, Julia; Llinares, Ana; Nikula, Tarja (Frontiers in Education, 2025)
Educationalists across the world aim to prepare their students for the realities of post-school life, be that at university or in the workplace. Increasingly, the expectations on school leavers have diversified also with regard to their linguistic abilities and prominently include subject-specific or disciplinary literacies, which encompass both knowledge of content and ways of conveying it in subject-specific ways. The global status of English has fostered the situation where subject-specific literacies are now not only needed in the main language of education, often the first language (L1) of students and teachers alike, but also in English as the strongest global lingua franca in both educational and professional environments. While this aim of achieving bi- or multilingual disciplinary literacies is implicitly present in all Content and Language Integrated Learning (CLIL) classrooms, the precise means of fostering such literacies vary across contexts. This article will outline work by the research network CLILNetLE (www.clilnetle.eu), which brings together over 240 individuals from 32 countries and is funded by the European Union. CLILNetLE aims to develop and refine the conceptualization of disciplinary literacies in CLIL taking into account research into (a) specific subjects (history, science, and mathematics), (b) challenges across school levels, including the expectations made in curricula, and (c) the influence of out-of-school and digital practices. To illustrate the multi-faceted nature of literacies, we will home in on one discursive aspect, i.e., Cognitive Discourse Functions and exemplify their use across levels, subjects, curricula, and digital practices. Drawing on this, we will outline how specific points of subject-specific literacies can and should be highlighted in teaching.